Thermoplastic composite manufacture using ara (Ficus sp.) sawmill sawdust - Nayan, Ahmad Fahmi (2002)
Research for thermoplastic composite manufacture from Ara (Ficus sp.) has been done. Ficus sp. was selected as a main raw material that is found from Forest Reserve University of Technology MARA (UiTM) Pahang. Polypropylene was used as a bounder between sawdust and used in the thermoplastic composite manufactured. Ficus sp. has a light yellow-brown in the sapwood. The sapwood is not differentiated from the heartwood. 5%, 10% and 15% sawdust has been choosing for this research. The tests that already done in the research were bending, tensile and the immersion test. As a result, 15% sawdust is more suitable. It refers to the result at higher bending, tensile and the immersion test. Therefore, as a result, details research about Ficus sp. should been carry out, which is can increase more uses in wood industries.